Faktor–Faktor yang Berhubungan dengan Kenyamanan, Beban Gejala, dan Depresi pada Pasien Kanker Payudara - Mustafidz, Mustafidz; Nuraini, Tuti; Hargiana, Giur; Gayatri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to evaluate factors associated with comfort, symptom burden, and depression in breast cancer patients. The method used was a systematic review following PRISMA guidelines, with searches in PubMed, Embase, and ScienceDirect until March 2024 using the terms